Patagonian inland water malacostracans as host for parasites - Rauque Perez, Carlos Alejandro (2013)
The host-parasite interactions of inland water malacostracans have been poorly studied. The aim of the present study is to provide an overview of parasites recorded for these hosts and to study the ecological implications of host-parasite relations. According to the literature, these parasites have exotic or native fishes, and aquatic birds as definitive hosts. As most definitive and all intermediate hosts are endemics, the parasite species are endemics as well.